Concentración de selenio en agua y en fracciones de sedimentos del río Catatumbo - Torres, Julio; Colina, Marinela; Nohemi, Yulixis; Rivas, Zulay; Andrade, Charity (Multiciencias, 2015)
Ver resumen PDF.